Students' Problem-Solving Skills: A Descriptive Study in High School Biology Education - Oriny Tri Ananda; Susriyati Mahanal; Hendra Susanto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Problem-solving skills are essential competencies in biology learning, which have a broad and complex scope closely related to real-life phenomena. Students are expected not only to understand biological concepts theoretically but also to apply them in formulating solutions to contextual problems. This study aims to analyse students’ problem-solving skills in biology learning at the senior high school level. The research employed a quantitative descriptive method with a sample of 105 students from SMA Negeri 11 Makassar, selected through random sampling. The research instrument consisted of 16 essay items developed based on eight indicators of problem-solving skills proposed by Greenstein. Data were analysed descriptively by calculating the percentage of achievement for each indicator. The results show that students’ problem-solving skills fall into the low category with an average percentage of 51.62%. The highest achievement was found in the ‘identifies solutions’ indicator (57.50%), while the lowest was in the ‘evaluates solutions’ indicator (47.86%). These findings highlight students’ difficulties in identifying complex biological problems, applying systematic problem-solving steps, evaluating the effectiveness of solutions, and connecting them to real-life contexts. Therefore, students’ problem-solving skills need to be improved through innovative, problem-based, and contextual learning strategies. This study emphasises the significance of active learning approaches in ensuring that biological concepts are not only understood conceptually but also applied meaningfully to address real-world challenges.